f(x) = 6 + CUBESQUAREROOT X 3 x f −1(x) =

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

f(x) = 6 + CUBESQUAREROOT X

3x

f −1(x) = 

Mar 1st, 2015

y = 6 + x^(1/3)

x = 6 + y^(1/3)

x - 6 = y^(1/3)

y = (x-6)^3

Mar 1st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 1st, 2015
...
Mar 1st, 2015
Oct 18th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer